(3MOjK CHj Ydi CMeO Hf GdaVd Hf GdYHGS Hf NRjeIs - (3YHO Gdedc Hf eMeO Hf YHO Gddg Hf HTQGf GdCehj HGdhdGA, CHh GdbGSe,J (B430 (3g` s
(3ChdgG (B:s
(3MOKfG CHh GdbGSe YHO Gdedc Hf eMeO Hf YHO Gddg Hf HTQGf bQGAI Ydjg ai Pi GdbYOI ef SfI SHY hYTQjf hCQHYeGFI s
(3BNQgG (B:s
(3MdaJ dCJjLf dge aJfI CJQc GdYGde efge MjQGf BNQ GdLR AGdKGdK ef MOjK GHf NRjeI s
(3GdfSNI efbhdg Yf fSNI YdjgG SeGYGJ HYVgG SfI (B427s
(3YdjgG SeGYGJ HYVgG SfI (B509 (3hHYVgG SfI (B559 (3hHYVgG SfI (B623 (3hai ChdgG NWhW LeGYI ef GdYdeGA efge GdMGaX GHf cKjQs
(3heMeO Hf eMeO GdNVjQi Ke SeGYGJ Ydi YHO Gddg Hf GddjKis
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs